Human nature as capacity : transcending discourse and classification - Rapport, Nigel, 1956- (Methodology and history in anthropology, 2010)
What is it to be human? What are our specifically human attributes, our capacities and liabilities? Such questions gave birth to anthropology as an Enlightenment science. This book argues that it is again appropriate to bring "the human" to the fore, to reclaim the singularity of the word as central to the anthropological endeavor, not on the basis of the substance of a human nature "To be human is to act like this and react like this, to feel this and want this" but in terms of species-wide capacities: capabilities for action and imagination, liabilities for suffering and cruelty. The contributors approach "the human" with an awareness of these complexities and particularities, rendering this volume unique in its ability to build on anthropology's ethnographic expertise